Predictors of successful chronic total occlusion percutaneous coronary interventions: a systematic review and meta-analysis. Issue 6 (6th October 2017) - Wang, Nelson; Fulcher, Jordan; Abeysuriya, Nishan; Adams, Mark; Lal, Sean
Abstract : Objective: The aim of this study was to identify positive and negative predictors of technical and clinical success for percutaneous coronary intervention (PCI) of chronic total occlusions (CTO). Methods: We conducted a systematic review and meta-analysis of studies published between 2000 and 2016 analysing rates of CTO PCI success with respect to demographic and angiographic characteristics. Crude ORs and 95% CIs for each predictor were calculated using a random effects model. Predictors of technical and clinical success were assessed among 28 demographic and 31 angiographic variables. Clinical success was defined as technical success without major adverse cardiac events. Results: A total of 61 studies, totalling 69 886 patients were included in this analysis. The major demographic characteristics associated with a 20% or greater reduction in the odds of technical and clinical success were a history of myocardial infarction, PCI, coronary artery bypass grafting, stroke/transient ischaemic attack and peripheral vascular disease. Angiographic factors were generally stronger predictors of reduced technical and clinical success. Those associated with >20% odds reduction included non-left anterior descending CTOs, multivessel disease, presence of bridging collaterals, moderate-to-severe calcification, >45 degree vessel bending, tortuous vessel, blunt stump and ostial lesions. Of these, novel predictors included prior PCI, prior stroke, peripheral vascular disease, presence of multivessel disease and bridging collaterals. Conclusion: The present study has identified strong negative predictors for clinical success for CTO PCI, which will aid in patient selection for this procedure.